Farmers’ Satisfaction towards the Agriculture Insurance: A Case of Chitwan and Kaski Districts of Nepal (The International Research Journal of Management Science, 2023)
Purpose: Subsidy based agriculture insurance schemes is flagship insurance program of Nepal which was started in Nepal one decade before. This paper aims to identify the factors influencing the satisfaction of agriculture insurance policyholders.Design/Methodology/Approach: Primary data were collected in Bharatpur and Pokhara metropolis of Nepal using structured questionnaire among 400 agriculture insurance policyholders who have already received claims or whose claim was in settlement process or whose claim was rejected by the insurer. Sample was selected using purposive and cluster sampling methods. Data were analysed through Mean, ANOVA, Wilk's Lamda and MANOVA tools.Findings: Age, landholding size, self-reported perception of insurance companies' service quality, and agriculture insurance types are insignificant while location of respondents, education level, food sufficiency of family, size of the farming, and respondents' assets are significant factors for policyholders' satisfaction towards the agriculture insurance. Timely settlement of claims increases the level of satisfaction. Nepal Insurance Authority and the Ministry of Agriculture Development need to review the existing directives to improve the agriculture insurance program. Insurance companies are suggested to offer prompt and quality services to policyholders and carry out educational campaign to increase customer awareness.Originality/Value: The study identified pertinent variables significant and indifference to farmers' satisfaction towards agriculture insurance. It also digs out the role of financial and nonfinancial aspects of insurance services. The study opens the door for further research on similar issues to enhance the existing body of knowledge.Implications: The demand for agriculture insurance is not increased significantly even large amount of subsidy in premium was provided. Present study may be useful to insurance companies, agents, regulators, the Ministry of Agriculture Development, researchers, and practitioners. The study can be used as a reference by managers of insurers to formulate the future strategies to enhance the agriculture insurance market.